Liver receptor homolog‐1 is a critical determinant of methyl‐pool metabolism. Issue 1 (10th October 2015) - Wagner, Martin; Choi, Sungwoo; Panzitt, Katrin; Mamrosh, Jennifer L.; Lee, Jae Man; Zaufel, Alex; Xiao, Rui; Wooton‐Kee, Ruth; Ståhlman, Marcus; Newgard, Christopher B.; Borén, Jan; Moore, David D.
Abstract : Balance of labile methyl groups (choline, methionine, betaine, and folate) is important for normal liver function. Quantitatively, a significant use of labile methyl groups is in the production of phosphatidylcholines (PCs), which are ligands for the nuclear liver receptor homolog‐1 (LRH‐1). We studied the role of LRH‐1 in methyl‐pool homeostasis and determined its metabolic effects using the methionine and choline–deficient (MCD) diet, which depletes methyl groups and results in a deleterious decrease in the PC‐to‐phosphatidylethanolamine ratio. We found that MCD diet–fed, liver‐specific LRH‐1 knockout mice ( Lrh‐1 –/– ) do not show the expected decreased methyl‐pool and PC/phosphatidylethanolamine ratio and are resistant to the hepatitis and fibrosis normally induced by the diet. Adaptive responses observed in wild‐type mice on the MCD diet were also observed in Lrh‐1 –/– mice on a normal diet. This includes reduced expression of the highly active glycine‐n‐methyltransferase and the biliary phospholipid floppase multidrug‐resistance protein 2 (Mdr2/Abcb4), resulting in reduced consumption of methyl groups and biliary PC secretion. In vitro studies confirm that Gnmt and Mdr2 are primary LRH‐1 target genes. Additional similarities between hepatic gene expression profiles in MCD diet–fed wild‐type and untreated Lrh‐1 –/– mice suggest that methyl‐pool deficiency decreases LRH‐1 activity, and this was confirmed by in vitro functional results in cells maintained in MCD medium. Conclusion : LRH‐1 is a novel transcriptional regulator of methyl‐pool balance; when the methyl‐pool is depleted, decreased LRH‐1 transactivation suppresses expression of key genes to minimize loss of labile methyl groups. (Hepatology 2016;63:95–106)